2018
DOI: 10.1177/0260106018791856
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised controlled trial of a sugar-sweetened beverage intervention in secondary schools: Pilot study protocol

Abstract: The high intake of SSB in adolescents has been consistently linked to having overweight and obesity, hence, interventions in this area should be prioritised. This pilot study intends to address identified evidence gaps by piloting the first intervention in Australia of its kind to reduce SSB intake in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…We conducted trial register searches to identify ongoing studies, and found 10 studies which we judged likely to meet our eligibility criteria upon completion. These include four studies on improved availability of drinking water in schools (Kajons 2018; NCT02996422; NCT03069274; NCT03181971), two studies on improved availability of low‐calorie beverages in the home environment (NCT02877823; NCT0306927), and one study each on reduced availability of SSB and improved availability of drinking water in schools (Oi 2018), reduced availability of SSB in workplaces (NCT03431051), price increases on SSB (NCT02914821) and the removal of SSB from supermarket checkout coolers (NCT03518151). We provide details of these studies in the section Characteristics of ongoing studies.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted trial register searches to identify ongoing studies, and found 10 studies which we judged likely to meet our eligibility criteria upon completion. These include four studies on improved availability of drinking water in schools (Kajons 2018; NCT02996422; NCT03069274; NCT03181971), two studies on improved availability of low‐calorie beverages in the home environment (NCT02877823; NCT0306927), and one study each on reduced availability of SSB and improved availability of drinking water in schools (Oi 2018), reduced availability of SSB in workplaces (NCT03431051), price increases on SSB (NCT02914821) and the removal of SSB from supermarket checkout coolers (NCT03518151). We provide details of these studies in the section Characteristics of ongoing studies.…”
Section: Resultsmentioning
confidence: 99%
“…A modelling study shows that the reduction in free sugars added to SSBs, without the use of artificial sweeteners, is predicted to reduce the prevalence of overweight, obesity and type 2 diabetes [19]. The high intake of SSBs in adolescents has been consistently linked to overweight and obesity; hence, interventions in this area should be prioritised [20]. To confirm this data, there is an increasing body of evidence that suggests that decreasing consumption of SSBs can impact positively on childhood overweight and obesity [21].…”
Section: Overweightmentioning
confidence: 99%
“…Secondary schools in Australia cater for students aged between 12 and 18 years. A full description of the trial methods is reported in the published protocol 27 …”
Section: Methodsmentioning
confidence: 99%
“…Following recruitment and baseline data collection, participating schools were randomised. Further recruitment and randomisation details can be found in the protocol for this study 27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation